Multiobjective Optimization of Biomass to Energy Supply Chains in an Uncertain Environment - Yilmaz Balaman, Şebnem; Selim, Hasan (Computer Aided Chemical Engineering, 2014)
The aim of this study is to design supply chain network for biomass to energy conversion systems for the regions having high potential of animal wastes and energy crops production and to reveal economical and environmental benefits from these systems. To this aim, a fuzzy multiobjective mixed integer linear programming (MILP) model is constructed. The model includes environmental and monetary objectives and it is structured as a multiperiod model in order to consider variation in the parameters. The model is solved by using different fuzzy goal programming (FGP) approaches.